Further Algebra: Skills Check

Download as pdf or txt
Download as pdf or txt
You are on page 1of 12

7

Further algebra
Skills check 4. Let
2x − 1 A
≡ +
B
x (2 x + 1) x 2x + 1
1. Coefficients of x2: A = 1
Coefficients of x: −4 = B ⇒ B = −4 ∴ 2x − 1 ≡ A (2x + 1) + Bx

Constant terms: 9 = −C ⇒ C = −9 Let x = 0, then   −1 = A(1) ⇒ A = −1


1 ⎛ 1⎞
2. Coefficients of x2: 3A = 6 ⇒ A = 2 Let x = − , then  −2 = B ⎜ − ⎟ ⇒B=4
2 ⎝ 2⎠
Coefficients of x: −2B = 8 ⇒ B = −4 −1 4
Ans: +
Constant terms: −2 = −2 + C ⇒ C = 0 x 2x + 1
3. Coefficients of x2: 1 – A = 8 ⇒ A = −7 2 x 2 + 17 x + 21 A B C
2 5. Let ≡ + +
Coefficients of x: −2 = −3B ⇒ B = ( x + 2)( x + 3)( x − 3) x + 2 x +3 x −3
3
∴ 2x 2 + 17x + 21
Constant terms: 5C = −10 ⇒ C = −2 ≡A
 (x + 3) (x − 3) + B (x + 2) (x − 3 ) + C (x + 2) (x + 3)
4. Coefficients of x2: 12 = 4A ⇒ A = 3 Let x = −2:  8 − 34 + 21 = A (1) (−5), −5 = −5A
1 ⇒A=1
Coefficients of x: 2B = 1 ⇒ B =
2
Let x = −3:  18 − 51 + 21 = B (−1) (−6), −12 = 6B
Constant terms: 0 = −7C ⇒ C = 0 ⇒ B = −2
5. Coefficients of x2: 2A = 6 => A = 3 Let x = 3:  18 + 51 + 21 = C (5) (6), 90 = 30 C
Coefficients of x: −3B = 0 ⇒ B = 0 ⇒C=3
1 2 3
Constant terms: 6 = 4 − 2C ⇒ C = −1 Ans: − +
x +2 x +3 x −3

Exercise 7.1A Exercise 7.1B


x −4 A B
1. Let ≡ + x

A
+
B
( x − 1)( x − 2) x − 1 x − 2 1. Let   ∴ x ≡ A(x − 2) + B
( x − 2) 2
x − 2 ( x − 2)2
∴x − 4 ≡ A(x − 2) + B(x − 1)
Let x = 2:   2 = B
Let x = 1, then −3 = A(−1) ⇒A=3
Let x = 2, then −2 = B(1) ⇒ B = −2 Let x = 1:   1 = A(−1) + B,   1 = −A + 2   ⇒ A = 1
3 2 1 2
Ans: − Ans: +
x −1 x − 2 x − 2 ( x − 2)2
x A B 3 A B C
2. Let ≡ + 2. Let ≡ + +
( x + 1)( x − 4 ) x + 1 x − 4 x (3 x − 1) 2
x 3 x − 1 (3 x − 1)2
∴x ≡ A(x − 4) + B(x + 1)
1 ∴ 3 ≡ A (3x − 1) (3x − 1) + Bx (3x − 1) + Cx
⇒A=
Let x = −1, then  −1 = A(−5)  
5 Let x = 0:   3 = A (−1) (−1)   ⇒ A = 3
4
Let x = 4, then   4 = B(5)  ⇒ B = 1
3 = C ⎜⎛ ⎞⎟     ⇒ C = 9
1
5 Let x = :   
1 4 3 3 ⎝ ⎠
Ans: +
5( x + 1) 5( x − 4 ) Equating coefficients of x 2 :
3x + 5 A B
3. Let ≡ + 0 = 9A + 3B, 0 = 27 + 3B ⇒ B = −9
( x + 3)( x − 1) x + 3 x − 1
3 9 9
∴ 3x + 5 ≡ A(x − 1) + B(x + 3) Ans: − +
x 3 x − 1 (3 x − 1)2
Let x = 1, then    8 = B(4) ⇒B=2
Let x = −3, then  −4 = A(−4) ⇒A=1
1 2
Ans: +
x +3 x −1
© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 1
x A B C 2(1 − x 2 ) A Bx + C
3. Let ≡ + + 2. Let ≡ +
( x − 1)( x − 2) 2
x − 1 x − 2 ( x − 2)2 x (2 + x 2 ) x 2 + x2

∴ x ≡ A(x − 2)2 + B(x − 1) (x − 2) + C(x − 1) ∴2 − 2x 2 ≡ A(2 + x 2) + x (Bx + C)


Let x = 1: 1 = A (1) ⇒A=1 Let x = 0: 2 = A (2) A=1
Let x = 2: 2 = C (1) ⇒C=2 Coefficients of x 2:  −2 = A + B,  −2 = 1 + B  ⇒ B = −3

Equating coefficients of x 2: Coefficients of x :   0 = C


1 3x
0 = A + B, 0 = 1 + B ⇒ B = −1 Ans: −
x 2 + x2
1 1 2
Ans: − + 13 x 2 + 2 x − 13 A Bx + C
x − 1 x − 2 ( x − 2)2 3. Let ≡ + 2
( x + 2)(2 x − 1)
2
x +2 2x − 1

1 A B C 13x2 + 2x – 13 ≡ A(2x2 − 1) + (Bx + C)(x + 2)


4. Let ≡ + +
( x + 1)( x − 1) 2
x + 1 x − 1 ( x − 1)2 Let x = −2, then 52 − 4 − 13 = A(8 − 1) ⇒ A = 5
∴ 1 = A(x − 1)2 + B(x + 1) (x − 1) + C(x + 1) Coefficients of x2: 13 = 2A + B, 13 = 10 + B ⇒ B = 3
1 Constant terms: −13 = −A + 2C, −13 = −5 + 2C ⇒ C = −4
Let x = −1: 1 = A (4) ⇒A=
4 5 3x − 4
1 Ans: + 2
Let x = 1: 1 = C (2) ⇒C= x +2 2x − 1
2
5 Ax + B C
Equating coefficients of x 2 : 4. Let ≡ 2 +
( x 2 + 4 )( x + 1) x +4 x +1
1 1
0 = A + B, + B 0= ⇒B= − 5 ≡ (Ax + B) (x + 1) + C (x 2 + 4)
4 4
1 1
+
1 Let x = −1:  5 = C(5)  ⇒ C = 1
Ans: −
4 ( x + 1) 4 ( x − 1) 2( x − 1)2 Coefficients of x 2:  0 = A + C,  0 = A + 1 ⇒  A = −1
1 A B C Constant terms:     5 = B + 4C,   5 = B + 4 ⇒  B = 1
5. Let ≡ + +
x ( x − 1) 2
x x − 1 ( x − 1)2 1− x 1
Ans: +
x +4
2
x +1
∴ 1 = A (x − 1)2 + Bx (x − 1) + Cx
16 x 2 − 13 x − 44 A Bx + C
Let x = 0: 1 = A(1) ⇒A=1 5. Let ≡ +
(5 − x )(4 x 2 − 3) 5− x 4x2 − 3
Let x = 1: 1 = C(1) ⇒C=1 16x2 − 13x − 44 ≡ A(4x2 − 3) + (Bx + C)(5 − x)

Equating coeff  icients of x 2: Let x = 5, then 400 – 65 − 44 = A(100 − 3), 291 = 97A
⇒A=3
0 = A + B, 0 = 1 + B ⇒ B = −1
1 1 1 Coefficients of x2: 16 = 4A − B, 16 = 12 − B ⇒ B = −4
Ans: − +
x x − 1 ( x − 1)2 Constant terms: −44 = −3A + 5C, −44 = −9 + 5C
⇒C=7
Exercise 7.1C 3 4x + 7
Ans: −
1 − 5x − 2 x 2
A Bx + C 5− x 4x2 − 3
1. Let ≡ + 2
(1 − x )( x + 2) 1 − x
2
x +2 3−x A Bx + C
6. Let ≡ +
∴ 1 − 5x − 2x  ≡ A (x  + 2) + (Bx + C ) (1 − x)
2 2 (1 − 2 x )(1 + x 2 ) 1 − 2 x 1 + x2

Let x = 1: 1 −5 − 2 = A(1 + 2),  −6 = 3A ⇒ A = −2 ∴ 3 − x ≡ A (1 + x 2) + (Bx + C) (1 − 2x)

Coefficients of x 2:  −2 = A − B,  −2 = −2 − B ⇒ B = 0 Let x = 2 :  2 2 = A 1 + 4 ⇒  A = 2


1 1
( 1
)  
⇒B=1
Coefficients of x 2:  0 = A − 2B,  0 = 2 − 2B  
Constant terms:  1 = 2A + C,  1 = −4 + C ⇒ C = 5
5 2 Constant terms:    3 = A + C,      3 = 2 + C  ⇒C=1
Ans: 2 − 2 x +1
x + 2 1− x Ans: + 2
1 − 2x 1+ x

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 2
7x − 4x 2 Ax + B C 1 A B
7. Let ≡ + Let ≡ +
(3 − x 2 )( x − 2) 3 − x2 x −2 ( x − 1)( x + 1) x − 1 x + 1

∴ 7x − 4x 2 ≡ (Ax + B) (x − 2) + C (3 − x 2) ∴ 1 ≡ A(x + 1) + B(x − 1)


Let x = 2: 14 − 16  = C (3 − 4),  −2 = −C ⇒ C = 2 1
⇒A=
Let x = 1, then   1 = A(2)  
2
Coefficients of x 2: −4 = A − C,  −4 = A − 2 ⇒
A = −2 1
Let x = −1, then   1 = B(−2)  ⇒ B = −
2
Constant terms: 0 = −2B + 3C, 0 = −2B + 6 ⇒ B = 3 1 1
Ans: 1 + −
3 − 2x 2 2( x − 1) 2( x + 1)
Ans: +
3 − x2 x −2 3
)
3. x 3 − 3x 2 + 4x − 12 3x 3 − 5 x 2 − 3x − 40
−22 x 2 + x − 5
8. Let ≡ A + Bx + C2 3x 3 − 9 x 2 + 12 x − 36
(2 x + 1)(2 + 3 x 2 ) 2x + 1 2 + 3x
4 x 2 − 15 x − 4
−22x2 + x – 5 ≡ A(2 + 3x2) + (Bx + C)(2x + 1) 4 x 2 − 15 x − 4 Ax + B C
Let ≡ 2 +
1 22 1 3 ( x 2 + 4 )( x − 3) x +4 x −3
Let x = − : − − − 5 = A  2 +  ,
2 4 2  4
4x 2 − 15x − 4 ≡ (Ax + B) (x − 3) + C(x 2 + 4)
−22 − 2 − 20 = A(8 + 3), −44 = 11A ⇒ A = −4
Let x = 3: 36 − 45 − 4 = C(13), −13 = C(13)
Coefficients of x2: −22 = 3A + 2B, −22 = −12 + 2B ⇒ C = −1
⇒ B = −5
Coefficients of x 2:  4 = A + C = A − 1 ⇒
Constant terms: −5 = 2A + C, −5 = −8 + C ⇒ A=5
C=3
Constant terms:     −4 = −3B + 4C = −3B − 4 ⇒
3 − 5x 4
Ans: − B=0
2 + 3x 2 2x + 1
5x 1
Ans: 3 + −
x +42
x −3
Exercise 7.1D
−1
1
1. x 2 − 5x + 6 x 2 ) +5 )
4. x 2 + 6x + 9  − x 2 − 8 x − 11
−x 2 − 6 x − 9
x2 − 5x + 6
− 2x − 2
5x −1
−2 x − 2 A B
Let ≡ +
x2 + 5 5x − 1 x 2 + 6 x + 9 ( x + 3) ( x + 3) 2
=1+
( x − 2)( x − 3) ( x − 2)( x − 3)
−2x − 2 ≡ A(x + 3) + B
5x − 1 A B
Let ≡ + Let x = −3:     + 4 = B ⇒   
B=4
( x − 2)( x − 3) x − 2 x − 3
Coefficients of x:  −2 = A ⇒  A = −2
∴ 5x − 1 ≡ A(x − 3) + B(x − 2)
2 4
Ans: −1 − +
Let x = 2, then 9 = A(−1) ⇒ A = −9 x + 3 ( x + 3) 2

Let x = 3, then 14 = B(3 − 2) ⇒ B = 14 −2  


)
2x − 8
5. x 2 − 4 −2 x 2 + 2 x +   ∴ A = −2
x2 − 4
9 14
Ans: 1 − + −2 x 2 +8
x −2 x −3
2x − 8
1 2x − 8 B C
)
1 Let = +
2. x 2 − 1 x 2   =1+ ( x + 2)( x − 2) x +2 x −2
x −1 2

x2 −1
2x − 8 = B(x − 2) + C(x + 2)
1
x2 1 Let x = −2:  −12 = B(−4) ⇒   B = 3
∴ = 1+
( x − 1)( x + 1) ( x − 1)( x + 1) Let x = 2:   −4 = C(4) ⇒  C = −1
Ans: A = −2     B = 3    C = −1

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 3
Exercise 7.1E ⇒B=−2
Let x = 2, then   − 6 = B(3)   
3 2
x −1 A B Ans: −
1. ≡ + x +1 x −2
( x + 1)( x + 3) x + 1 x + 3
3
x − 1 ≡ A (x + 3) + B (x + 1) 6.
3x 2 + 5x + 3
x 2 − 3x
)
  x − 3x 3x + 5x + 3
2 2

Let x = −1, then  −2 = A(2)  ⇒ A = −1 3x 2 − 9 x


Let x = −3, then  −4 = B(−2)  ⇒ B = 2 14 x + 3

Ans: −1 + 2
Let
14 x + 3 A
≡ +
B
x +1 x +3 x ( x − 3) x x −3
x 2 − 4x + 3
2. 14x + 3 ≡ A(x − 3) + Bx
x 2 + 3x + 2
1 Let x = 0, then   3 = A( − 3)  ⇒ A = − 1
2
)
x   + 3x + 2 x − 4 x + 3  = 1 +
2 −7 x + 1
( x + 1)( x + 2)
⇒ B = 15
Let x = 3, then  45 = B(3)    
x + 3x + 2
2

− 7x + 1 Ans: 3 − 1 + 15
x x −3
−7 x + 1 A B
Let ≡ + 1 + 3x 2 A B C
( x + 1)( x + 2) x − 1 x + 2 7. ≡ + +
x ( x − 1)2 x x − 1 ( x − 1)2
−7x + 1 ≡ A(x + 2) + B(x + 1)
1 + 3x 2 ≡ A (x − 1)2 + Bx (x − 1) + Cx
⇒A=8
Let x = −1, then   8 = A(1)  
Let x = 0, then  1 = A( − 1)2  ⇒ A = 1
Let x = −2, then  15 = B(−1)  ⇒ B = −15
Let x = 1, then  4 = C    ⇒ C = 4
8 15
Ans: 1 + − Coefficients of x 2:  3 = A + B = 1 + B ⇒  B = 2
x +1 x +2
1 2 4
2x − 7 A B Ans: + +
3. ≡ + x x − 1 ( x − 1)2
( x − 5) 2 x − 5 ( x − 5) 2
2x 2 − 3 A Bx + C
2x − 7 ≡ A (x − 5) + B 8. ≡ + 2
x ( x + 2)
2
x x +2
Let x = 5:     3 = 0 + B  ⇒ B = 3
2x 2 − 3 ≡ A(x 2 + 2) + (Bx + C)x
Coefficients of x:    2 = A   ⇒ A = 2 −3
Let x = 0, then  −3 = A(2)  ⇒ A =
2 3 2
Ans: + −3 7
x − 5 ( x − 5) 2 Coefficients of x 2:  2 = A + B = + B  ⇒ B =
2 2
11x + 3 A Bx + C Coefficients of x:    0 = C
4. ≡ +
(1 − 5 x )(1 + x ) 1 − 5 x
2
1 + x2 −3 7x
Ans: +
2 x 2 ( x 2 + 2)
11x + 3 ≡ A(1 + x 2) + (Bx + C)(1 − 5x)
x −1 A B
  x − 1 ≡ A(x + 1) + Bx
Let x = : 
1
5
11
5
+3=A1+
1
25 (
, 
130
25
)
= A ⎛⎜ ⎞⎟
26
⎝ 25 ⎠
9. ≡ +
x ( x + 1) x x + 1

130 Let x = 0, then   −1 = A(1)     ⇒ A = − 1


⇒A= =5
26 Let x = −1, then  −2 = B(−1)  ⇒ B = 2
Coefficients of x  : 0 = A − 5B = 5 − 5B ⇒ B = 1
2
1 2
Ans: − +
x x +1
Constant terms:     3 = A + C, 3 = 5 + C ⇒ C = − 2
5 x −2 1
Ans: +
1 − 5x 1 + x2 10. x  − 9 x + 2 x
2 2

x2 −9
x −8 A B
5. ≡ + 2x + 9
( x + 1)( x − 2) x +1 x −2
2x + 9 A B
x − 8 ≡ A(x − 2) + B(x + 1)  Let ≡ +
( x + 3)( x − 3) x + 3 x − 3
Let x = − 1, then  − 9 = A( − 3)  ⇒ A = 3

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 4
 2x + 9 ≡ A (x − 3) + B (x + 3)  Let x = − 2:  8 − 4 + 3 = A(4 + 3)  ⇒ A = 1
−3 −1
 Let x = −3:  3 = −6A + 0 ⇒  A = =  Coefficient x 2:  2 = A + B = 1 + B  ⇒ B = 1
6 2
5  Constant:  3 = 3A + 2C = 3 + 2C  ⇒ C = 0
 Let x = 3:  15 = 0 + 6B  ⇒ B = 15 = 1 x
6 2  Ans: + 2
5 1 x +2 x +3
 Ans: 1 + −
2( x − 3) 2( x + 3)
8x 2 + 5x + 3 A B C Exercise 7.2
11. ≡ + +
( x − 2 )( x + 1) x − 2 x + 1 ( x + 1)2 ( −4 )( −5)
2
1. a) (1 − x)−4 = 1 + (−4) (−x) + (−x)2
2
8x 2 + 5x + 3 ≡ A
 (x + 1) 2 + B (x − 2)(x + 1) ( −4 )( −5)( −6)
+ (−x)3
+ C (x − 2) 3×2
Let x = 2:  32 + 10 + 3 = A(9) ⇒    A = 5 = 1 + 4x + 10x 2 + 20x 3 + ...
Let x = − 1:  8 − 5 + 3 = C(−3) ⇒    
C = −2 for −1 < − x < 1,  i.e. − 1 < x < 1
Coefficients of x 2:  8 = A + B = 5 + B   ⇒ B = 3 ( −5)( −6)
(1 + 3x)−5 = 1 + (−5) (3x) +
b) (3x)2
5 3 2 2
Ans: + − ( −5)( −6)( −7 )
x − 2 x + 1 ( x + 1)2 + (3x)3
3×2
x −3 A Bx + C = 1 − 15x + 135 x 2 − 945x 3
12. ≡ +
( x − 1) ( x 2
+ 1) x −1 x 2 +1
for −1 < 3x < 1,  i.e. − < x <
1 1
3 3
x − 3 ≡ A(x 2 + 1) + (Bx + C)(x − 1)
⎛ 1 ⎞ ⎛ −2 ⎞ ⎛ 1 ⎞ ⎛ −2 ⎞ ⎛ −5 ⎞
Let x = 1:  − 2 = A(2)        ⇒ A = − 1 1 ⎜ ⎟⎜ ⎟ 1 ⎜ ⎟⎜ ⎟⎜ ⎟
3 3 ⎝ 3 ⎠ ⎝ 3 ⎠ ⎝ 3 ⎠ x 3
(1 + x ) = 1 + x + ⎝ ⎠ ⎝ ⎠ x 2 +
c) 3
Coefficients of x  :  0 = A + B = − 1 + B  ⇒ B = 1
2
3 2 3×2
Constant terms:  −3 = A  − C = − 1 − C       ⇒ C = 2 1 1 5 3
=1+ x − x 2 + x    for −1 < x < 1
1 x +2 3 9 81
Ans: − +
x − 1 x2 + 1 x −3 ( −3)( −4 ) ⎛ x ⎞
2

) = 1 + (−3) ⎛⎜ ⎞⎟ +
x
(1 +
d) ⎜ ⎟
x A B C 2 ⎝2⎠ 2 ⎝2⎠
13. ≡ + +
( x − 1)( x − 2) 2
x − 1 x − 2 ( x − 2)2 ( −3)( −4 )( −5) ⎛ x ⎞
3

+ ⎜ ⎟
x ≡ A(x − 2)2 + B(x − 1)(x − 2) + C(x − 1) 3×2 ⎝2⎠
3 3 5
 Let x = 1:  1 = A(− 1)2  ⇒ A = 1 = 1 − x + x 2 − x 3 + ...
2 2 4
 Let x = 2:  2 = C (1)     ⇒ C = 2 x
for −1 < < 1,  i.e. for −2 < x < 2
2
 Coefficients of x 2:  0 = A + B = 1 + B  ⇒ B = −1 x
1 1 2 e) = x (1 − x)−1
 Ans: − + (1 – x )
x − 1 x − 2 ( x − 2)2 ( −1)( −2)
(1 − x)−1 = 1 + (−1) (−x) + (−x)2 + ...
1 2
14.
x2 + 1
x2 − 1
  x 2
− 1 x 2
+ 1 ) = 1 + x + x 2
x −1
2
∴ x (1 − x) = x (1 + x + x 2) = x + x 2 + x 3
2
for −1 < x < 1
2 2 A B
 Let = ≡ + ( −2)( −3)
x −1
2
( x + 1)( x − 1) x + 1 x − 1 (1 − 5x)−2 = 1 + (−2) (−5x) +
f) (−5x)2
2
 ∴ 2 ≡ A(x − 1) + B(x + 1) ( −2)( −3)( −4 )
+ (−5x)3 + ...
3×2
 Let x = − 1:  2 = A( − 2)  ⇒ A = − 1
= 1 + 10x + 75x 2 + 500x 3 + ...
⇒B=1
 Let x = 1:   2 = B(2)     1 1
for −1 < −5x < 1,  i.e for − < x <
1 1 5 5
 Ans: 1 − +
x +1 x −1
⎛ 1 ⎞⎛ 3 ⎞
−1 ⎜ − ⎟⎜ − ⎟
2x 2 + 2x + 3 A Bx + C ⎛ 1⎞ 2 ⎝ 2 ⎠ ⎝ 2 ⎠ (x 2)2 + ...
15. ≡ + 2 2. (1 + x ) = 1 + ⎜
2 2 − ⎟ (x  ) +
( x + 2)( x + 3) x + 2
2
x +3 ⎝ 2⎠ 2
1 3
 2x 2 + 2x + 3 ≡ A(x 2 + 3) + (Bx + C)(x + 2) = 1 − x 2 + x 4 + ...  for −1 < x < 1
2 8
© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 5
( −2)( −3) (1 + 2x) (1 − x)−2 = (1 + 2x) (1 + 2x + 3x 2 + 4x 3 +…)
3. a) (1 − x)−2 = 1 + (−2) (−x) + (−x)2
2
( −2)( −3)( −4 )  = 1 (1 + 2x + 3x 2 + 4x 3) + 2x (1 + 2x +
+ (−x)3
3×2 3x 2 +…)
= 1 + 2x + 3x 2 + 4x 3 + ...  for −1 < x < 1  = 1 + 2x + 3x 2 + 4x 3 + 2x + 4x 2
50th term = 50x 
b) 49
+ 6x 3 +…
⎛ 1 ⎞ ⎛ −1 ⎞
1
1 ⎜ ⎟⎜ ⎟     = 1 + 4x + 7x 2 + 10x 3 +…
⎝ 2 ⎠⎝ 2 ⎠
4. a) (1 – 2 x ) = 1 + (−2x) +
2 (−2x)2
2 2 for −1 < x < 1
⎛ 1 ⎞ ⎛ −1 ⎞⎛ −3 ⎞
⎜ ⎟ ⎜ ⎟⎜ ⎟ 1 ⎛ −1 ⎞ 1 ⎛ −1 ⎞ ⎛ −3 ⎞
2 2 2
+ ⎝ ⎠ ⎝ ⎠⎝ ⎠ (−2x)3 1
1 ⎜ ⎟ ⎜ ⎟⎜ ⎟
2 ⎝ 2 ⎠ 2 2 ⎝ 2 ⎠⎝ 2 ⎠ 3
3×2 8. a) (1 + x ) = 1 + x +
2 x  + x  +…
1 ⎛ −1 ⎞ ⎛ −3 ⎞ ⎛ −5 ⎞ 2 2 3× 2
⎜ ⎟⎜ ⎟⎜ ⎟ 1 1 1 3
2 2 2 2
+ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠ (−2x)4 =1+ x − x 2 + x  +…  for −1 < x < 1
4×3×2 2 8 16
1 2 1 3 5 4
= 1 −x − x  − x  − x  +… 1 + x = 1.08  x = 0.08
b)
2 2 8
1 1 1
1 1  1.08 = 1 + (0.08) − (0.08) 2 + (0.08)3 +…
for −1 < −2x < 1,  i.e. for − < x < 2 8 16
2 2
 = 1 + 0.04 − 0.0008 + 0.000 032 = 1.0392
1 − 2x = 0.8
b) 0.2 = 2x x = 0.1
1 1 5 n (n −1)
 0.8 = 1 − 0.1 − (0.1)2 − (0.1)3 − (0.1)4 9. a) (1 + ax)n = 1 + n (ax) + (ax)2 +…
2 2 8 2
n (n −1) 2 2
 = 1 − 0.1 − 0.005 − 0.0005 − 0.000 062 5 = 1 + nax + a x +…
2
= 0.8944
n (n −1) 2
∴ na = 4 and a = 10
⎛ −1 ⎞ ⎛ −3 ⎞ 2
−1
− ⎜ ⎟⎜ ⎟
⎛ ⎞1 ⎝ 2 ⎠⎝ 2 ⎠ 2
5. (1 + x ) 2 = 1 + ⎜ ⎟ x + x  4 n (n − 1) ⎛ 4 ⎞
2
n (n − 1) ⎛ 16 ⎞
⎝ 2 ⎠ 2 a = ∴ ⎜ ⎟ = 10,  ⎜ ⎟ = 10
n 2 ⎝n⎠ 2 ⎝ n2 ⎠
1 3
= 1 − x + x 2 +… 8
2 8 
(n − 1) = 10,  8n − 8 = 10n,  −8 = 2n, n = −4
−1
n
1 3
(1 − x) (1 + x ) 2 = (1 + x) (1 − x + x 2 +…) but na = 4 ∴ −4a = 4,  a = −1
2 8
1 3 1 Ans: a = −1,  n = −4
= 1 (1 − x + x 2 +…) − x(1 − x
2 8 2
+…) n (n − 1)(n − 2)
b) Term in x 3 = (ax)3
3×2
1 1
= 1 − x + 3 x 2 − x + x 2 +…
2 8 2 −4 ( −5)( −6)
  =  (−x)3 = 20x 3
3×2
3 7
= 1 − x + x 2 +…  for −1 < x < 1
2 8 Coefficient of x 3 = 20

( −2)( −3) ( −1)( −2) 2 2


6. (1 + 4x 2)−2 = 1 + (−2) (4x 2) + (4x 2)2 + 10. (1 + x 2)−1 = 1 + (−1) (x 2) + (x  )
2 2
( −2)( −3)( −4 ) = 1 − x 2 + x 4
(4x 2)3
3×2
  (1 − 3x) (1 + x 2)−1 = 1 (1 − x 2 + x 4) − 3x (1 − x 2 +…)
= 1 − 8x 2 + 48x 4 − 256x 6 +…
1 1  = 1 − x 2 + x 4 − 3x + 3x 3
for − < x <
2 2  = 1 − 3x − x 2 + 3x 3 + x 4
( −2)( −3)
7. (1 − x)−2 = 1 + (−2) (−x) + (−x)2  for −1 < x < 1
2
( −2)( −3)( −4 )
+ (−x)3 +… n (n − 1)
3×2 11. a) (1 + kx)n = 1 + n (kx) + (kx)2
2
= 1 + 2x + 3x 2 + 4x 3 +… = 1 + 12x + 81x 2

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 6
∴ nk = 12,  i.e. k =
2
12
n
and
n (n −1) 2
2
k   = 81 +
( −5)( −6 )( −7 )  x  3
3 × 2 ×1
 − 
2 ]
n (n − 1) ⎛ 12 ⎞
i.e.

n (n −1) (144 )
2
⎜ ⎟ = 81
⎝ n ⎠ =
1
32[ 5 15 35
1 +  x +  x 2 +  x 3 +…
2 4 8 ]
72(n − 1)
2
= 81  = 81 1 5 15 2 35 3
2 n n = + x+ x +  x  +…
32 64 128 256
72n − 72 = 81n
for −2 < x < 2
−72 = 9n,  n = −8
1 1
1 1
12 −3 ⎛ x ⎞2 ⎛ x ⎞2
If n = −8,  k = = 3. ( 4 − x ) = 4 ⎜ 1 − ⎟ = 2 ⎜ 1 − ⎟
2 2
−8 2 ⎝ 4⎠ ⎝ 4⎠

Ans: k =

b) Term in x =
−3
2
, n = −8

n (n − 1)(n − 2)
3
(kx)3
[
= 2 1 + ⎜ ⎟⎜ ⎟ +
⎝2⎠⎝ 4 ⎠
⎛ 1 ⎞⎛ 1 ⎞
⎜ ⎟⎜ − ⎟
⎛ 1 ⎞ ⎛ −x ⎞ ⎝ 2 ⎠ ⎝ 2 ⎠ ⎛ −x ⎞
2

⎝ 4 ⎠
2

⎟ +… ]
[ ]
3×2 1 1 2
3 = 2 1 −  x +  x  +…
( −8)( −9 )( −10 ) ⎛ −3 ⎞ 8 128
  = ⎜ x⎟
3×2 ⎝ 2 ⎠ 1 1 2
⎛ −27 ⎞ 3
= 2 −  x −  x  +…
  = −120 ⎜ 4 64
⎟ x  = 405x 
3
⎝ 8 ⎠ x
for −1 < − < 1,  i.e. for −4 < x < 4
4
12. (1 − 2x) (1 + 2x 2)−1 = (1 − 2x) [1 + (−1) (2x 2)

[( ) ] ( ) 1
x −1 x −1
( −1)( −2) 4. (3 + x)−1 = 3−1 1 + = 1+
+ (2x 2)2 +…] 3 3 3
2

[ ]
2
     = 1 (1 − 2x 2 + 4x 4) 1 x ( −1)( −2) ⎛ x ⎞
= (1 + (−1) + ⎜ ⎟ +…
3 3 2 ⎝3⎠
+ (−2x) [1 − 2x 2 +…]

     = 1 − 2x − 2x  + 4x  + 4x  +…


     = 1 − 2x  + 4x  − 2x + 4x  + ...
2

2
4

3
3

4
=
1
3[ x
1− +
3
x2
9
1 1
3 9
1
+… = − x +  x2 +…
27 ]
1
Ans:
27
Exercise 7.3
−1 −1 −1
1
−1 5. (2 + x2)−1 = 2−1 1 + ( 2 )
x 2 −1 1 
2
x2 
  = 1 + 
2
1. a) [25(1 − 2 x )] 2 = 25 2 (1 − 2 x ) 2 = (1 − 2 x ) 2

9(3
b) − x)−2 = 9 3−2 1 −   [ ( x
)]
−2
5
= 1 + (−1) ⎜
1
2 [ ⎛ x2 ⎞
⎝ 2 ⎠

]
3 2 3
( −1)( −2) ⎛ x 2 ⎞ ( −1)( −2)( −3) ⎛ x 2 ⎞

=9 [ (1 − ) ]
1 x −2 +
2
⎜ ⎟ +
⎝ 2 ⎠ 3×2
⎜ ⎟
⎝ 2 ⎠

[ ]
9 3 2 4 6
1 x x x
= 1− + −
x
( )
−2
2 2 4 8
= 1−
3
1 x2 x4 x6
1 = − + − +…
1 1 2 4 8 16
⎛ 4 ⎞ 3
(27
c) + 4 x ) 3  = 27 3 ⎜ 1 + x⎟
⎝ 27 ⎠ for − 2 < x < 2
1

= 3 ⎛⎜ 1 +
4 ⎞ 3

( )
x⎟ x −2
⎝ 27 ⎠ 6. a) (4 − x)−2 = 4−2 1 −
4

( x
) [
−5 2
(2 − x)−5 = 2−5 1 −   1 ⎛ x⎞ ( −2)( −3) ⎛ x ⎞
2.
2 =  1 + (−2) ⎜ − ⎟ + ⎜− ⎟
16 ⎝ 4⎠ 2 ⎝ 4⎠
1 x
=  1 + (−5) − +
32 2 [
( −5)( −6 )  x 
2
 − 
2 ( )
2

+
( −2)( −3)( −4 ) ⎛ x ⎞
3×2
⎜ ⎟
⎝4⎠
3

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 7
=
1 ⎡ 1 3 1 ⎤
1+ x + x2 + x3 ⎥
16 ⎢⎣ 2 16 16 ⎦
=
1
4 [ 3
1 − px + p 2 x 2 +…
4 ]
1 1 3 2 1 3 1 1 3 2 2
= + x+ x + x + ... − px + so p  x  = 11 + 6x + qx 2
16 32 256 256 4 4 16
1 3 2
for −4 < x < 4 ∴ −  p = 6,  p = −24  and   p  = q
4 16
(2 −
b)
1
16 32
1
+  x +
x) ( 3 2
256
 x  +
1
265
 x 3 ) 3
∴ (−24)2 = q  ∴ q = 108
16
⎛ 1 3⎞ ⎛ 3 ⎞ 2 Ans: p = −24,  q = 108
Term in x 3 = (2) ⎜ x ⎟ + (−x) ⎜ ⎟  x 
⎝ 256 ⎠ ⎝ 256 ⎠
1 ⎡ ( −2)( −3)( −4 ) ⎛ p ⎞ ⎤
3
2 3 3 3 ⎛ p3 3 ⎞
= x −  x  4th
b) term = ⎢ ⎜ x ⎟ ⎥ = (−1) ⎜ x ⎟
256 256 4⎣ 3×2 ⎝2 ⎠ ⎦ ⎝ 8 ⎠
1 (24 )3 3
Coefficient of x 3 = − =  x  = 1728 x 3
256 8
1 1
1 1 1 1
⎡ 1 ⎤2 ⎡ 1 ⎤2 1

1
k ⎞2 ⎛ k ⎞2
7. 9 − x = (9 − x )  = 9 ⎢1 − x ⎥   = 3 ⎢1 − x ⎥
2 2
10. ( 4 − kx ) = 4 ⎜ 1 − x ⎟ = 2 ⎜ 1 − x ⎟
2 2
⎣ 9 ⎦ ⎣ 9 ⎦

[ ]
⎝ 4 ⎠ ⎝ 4 ⎠

[ ]
⎛ 1 ⎞ ⎛ −1 ⎞
⎜ ⎟ ⎜ ⎟ −1 2 ⎛1⎞⎛ 1⎞
⎛ 1 ⎞ ⎛ −1 ⎞ ⎝ 2 ⎠⎝ 2 ⎠ ⎛ x ⎞ ⎜ ⎟ ⎜− ⎟ 2

= 3 1 + ⎜ ⎟ ⎜ ⎟ x + ⎜ ⎟ +… ⎛ 1 ⎞ ⎛ k ⎞ ⎝ 2 ⎠ ⎝ 2 ⎠ ⎛ −k ⎞
⎝2⎠⎝ 9 ⎠ 2 ⎝ 9 ⎠ = 2 1 + ⎜ ⎟ ⎜− x ⎟ + ⎜ x ⎟  +…
⎝2⎠⎝ 4 ⎠ 2 ⎝ 4 ⎠
1 1

[ ]
for − <x<
9 9 k k2 2
=21− x − x +…
1
8
1
72 [ 1
6
1
= 3 1 −  x +  x 2 +… = 3 − x +  x 2 +…
24 ] =2−
k
8

x −
k2 2
128

x +…
∴ (1 + 3x) 3 − ( 1
6
1
x +  x 2 +…
24 ) −k ⎛ −k 2 ⎞
4

−k
64

−k 2
1 1 2 1   ∴ = 8⎜ ⎟ ,   = ,  −2k = −k2
= 3 −  x +  x  + 9x −  x 2 +… 4 ⎝ 64 ⎠ 4 8
6 24 2
53 109 2 55  k2 − 2k = 0,   k(k − 2) = 0,   k = 2
= 3 +  x − −
x +…
6 216 3888
−1 −1
−1 −1 Exercise 7.4
⎡⎛ 1 2 ⎞⎤ 2 1⎛ 1 2⎞2
+ 2x ) = 4 ⎢⎜⎝ 1 + 2 x ⎟⎠ ⎥ = 2 ⎜⎝ 1 + 2 x ⎟⎠
2
8. ( 4 2 2
⎣ ⎦ 3x + 5 A B
1. a) ≡ +
  1 + ⎜− ⎟ ⎜ x ⎟ +
= 
2 1
2 [ ⎛ 1⎞⎛1
⎝ 2⎠⎝2


(1 − x )(1 + 3 x ) 1 − x

3x + 5 ≡ A(1 + 3x) + B(1 − x)


1 + 3x

⎛ −1 ⎞ ⎛ −3 ⎞ Let x = 1:  8 = A(1 − 3)  ⇒ A = 2


⎜ ⎟⎜ ⎟ 1 2
⎝ 2 ⎠⎝ 2 ⎠ ⎛ x2 ⎞
⎜ ⎟ −1 ⎛ 1⎞ 4
2 ⎝2 ⎠ Let x = :  −1 + 5 = B⎜ 1 + ⎟,  4 =  B  ⇒ B = 3
3 ⎝ 3⎠ 3
⎛ −1 ⎞ ⎛ −3 ⎞ ⎛ −5 ⎞ +
⎜ ⎟⎜ ⎟⎜ ⎟ 1 3
⎝ 2 ⎠⎝ 2 ⎠⎝ 2 ⎠ ⎛ x2 ⎞ + …
6
⎜ ⎟
⎝2 ⎠
] Ans:
2
1− x
+
3
1 + 3x

=   1 −  x 2 +
1
2 [ 1
4
3 4
32
 x  −
5 6
128
 x  +… ] 2(1
b) [
− x)−1 = 2 1 + (−1) (−x) +
( −1)( −2) 2
2
(x) +… ]
= 2 + 2x + 2x  +…2
1 1 2 3 4 515 6
=

for − 2 < x < 2


− x +
2 8 64
x −
256
1024
x  +…
[
3(1 + 3x)−1 = 3 1 + (−1) (3x) +
( −1)( −2)
2
(3x)2 +… ]
= 3 − 9x + 27x  +… 2
−2

= 2 (1 + x)−2 = ⎛⎜ 1 + x ⎞⎟
p 1 p −1 1
9. a) (2 + px) −2 −2
Ans: 5 − 7x + 29x 2 for <x<
2 4⎝ 2 ⎠ 3 3


1
4 [
= 1 + (−2) (  x)
p
2 2. a)
x2
(1 + 2 x ) (1 + x )
2

A
1 + 2x
+
B
1+ x
+
C
(1 + x )2

]
2
( −2)( −3) ⎛ p ⎞
+ ⎜ x ⎟ +… x2 ≡ A(1 + x)2 + B(1 + 2x) (1 + x) + C(1 + 2x)
2 ⎝2 ⎠

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 8
⇒ C = −1
Let x = −1:   1 = C(1 − 2)       Let x = 2:  8 − 22 + 16 = C (1 − 2)2  ⇒ C = 2
2
−1 1 ⎛ 1⎞ 1 Coefficients of x 2:  4 = A + C = A + 2  ⇒ A = 2
Let x =    = A ⎜ 1 − ⎟ = A  
⇒A=1
2 4 ⎝ 2⎠ 4
2 1 2
Coefficients of x 2:  1 = A + 2B = 1 + 2B  ⇒ B = 0 Ans: 1 − x + (1 − x )2 + 2 − x
1 1
Ans: − ( −1)( −2)
1 + 2x (1 + x )2 2 (1 − x)−1 = 2 [1 + (−1) (−x) +
b) (−x)2 +…]
2
( −1)( −2)
(1 + 2x)−1 = 1 + (−1) (2x) +
b) (2x)2  = 2 + 2x + 2x 2 +…
2
( −1)( −2)( −3) ( −2)( −3)
+ (2x)3 +… (1 − x)−2 = 1 + (−2) (−x) + (−x)2 +…
3×2 2
= 1 − 2x + 4x 2 −8x 3 +… = 1+ 2x + 3x 2

[ ]
−1 −1
( −2)( −3) 2
2 (2 − x)−1 = 2 2−1 ⎛⎜ 1 −
x⎞ ⎛ x⎞
(1 + x) −2
=1
 + (−2) (x) + (x) ⎟ +… = ⎜ 1 − ⎟
2 ⎝ 2⎠ ⎝ 2⎠
( −2)( −3)( −4 ) 3 ( −1)( −2) ⎛ x ⎞2
+ (x) +… = 1 + (−1) ⎛⎜ − ⎞⎟ +
x
3×2 ⎜− ⎟
2
⎝ 2⎠ ⎝ 2⎠
= 1 − 2x + 3x 2 − 4x 3 +… x x 2
=1+ +
Coefficient of x 2 = (−8) − (−4) = −4 2 4
9 21
x +2 x+ 2 A B Ans: 4 + x + x 2 + …  for −1 < x < 1
3. a) = ≡ + 2 4
x −1
2
( x + 1)( x − 1) x+1 x −1
1 A B
x + 2 ≡ A (x − 1) + B (x + 1) 5. a) ≡ +
(1 − x )( x − 2) 1− x x −2
Let x = −1:  −1 + 2 = A (−1 −1),
1 ≡ A (x − 2) + B (1 − x)
−1
+1 = −2A  ⇒ A =
2 Let x = 1:  1 = A (1 − 2)  ⇒ A = −1
3
Let x = 1:  1 + 2 = B (1 + 1)  ⇒ B =
2 Let x = 2:  1 = B (1 − 2)  ⇒ B = −1
1 3
Ans: − + −1 1 −1 1
2( x + 1) 2( x − 1) Ans: −  or  +
1− x x −2 1− x 2−x

b)
1
2
1
− (1 + x)−1 = − 1 + (−1)x +
2 2 [
( −1)( −2) 2
x
[
− (1 − x)−1 = − 1 + (−1) (−x) +
b)
( −1)( −2)
2
(−x)2 +… ]
( −1)( −2)( −3) 3
+
3×2
x +… ] = −1 − x − x2
−1
(2 − x)−1 = 2−1 ⎛⎜ 1 − x ⎞⎟
= − 1 + 1 x − 1 x2 + 1 x3 + … ⎝ 2⎠

[ ]
2 2 2 2 2
1 ⎛ − x ⎞ ( −1)( −2) ⎛ − x ⎞
3 3 −3 = 1 + (−1) ⎜ ⎟ + ⎜ ⎟ +…
(x − 1)−1 = [−1−1 (1 − x)−1] = (1 − x)−1 2 ⎝ 2 ⎠ 2 ⎝ 2 ⎠
2 2 2
1 1 1
= + x + x2

−3
[
=  1 + (−1) (−x) +
2
( −1)( −2)
2
(−x)2 2 4 8
1 −7
Coefficient of x 2 = −1 + =
+
( −1)( −2)( −3)
3×2
(−x)3 ] 1 A Bx + C
8 8

6. a) 2 ≡
+
−3 3 3 3 (1 − x )(1 + x ) 1 − x 1 + x2
= − x − x2 − x3 + …
2 2 2 2
1 ≡ A(1 + x 2) + (Bx + C) (1 − x)
Ans: −2 − x − 2x 2 − x 3  for −1 < x < 1
1
Let x = 1:  1 = A(2)  ⇒ A =
8 − 11x + 4 x 2
A B C 2
4. a) ≡ + 2 +
(1 − x )2 (2 − x ) 1− x (1 − x ) 2−x 1 1

Coefficients of x 2:  0 = A − B, 0 = −B⇒B=
2 2
8 − 11x + 4x 2 ≡ A
 (1 − x) (2 − x) + B (2 − x)
1 1
+ C (1 − x)2 Constant terms:  1 = A + C, 1 = +C ⇒ C =
2 2
Let x = 1:  8 − 11 + 4 = B (2 − 1) ⇒ B = 1
 1 x +1
Ans: +
2(1 − x ) 2(1 + x 2 )

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 9
1 1
[
b) (1 − x)−1 = 1 + (−1) (−x) +
2 2
( −1)( −2)
2
(−x)2 + Summary exercise 7


( −1)( −2)( −3)
3×2
(− x )3 +
( −1)( −2)( −3)( −4 )
4×3×2
(− x )4 +… ] 1. Let
3 x + 11

A
+
B
x2 − x − 6 x − 3 x + 2
1 1 1 1 1 3x + 11 ≡ A(x + 2) + B(x − 3)
= +  x +  x 2 +  x 3 +  x 4 + …
2 2 2 2 2 Let x = 3:  20 = A(5)   ⇒ A = 4
1
(x + 1) (1 + x 2)−1 Let x = −2:  5 = B (−5)  ⇒ B = −1
2
4 1

[ ]
1 Ans: −
( −1)( −2) 2 2 x −3 x +2
= (x + 1) 1 + (−1) (x 2) + (x  ) +…
2 2
2x − 1 A Bx + C
1 2. Let ≡ + 2
= (x + 1) (1 − x 2 + x 4 +…) ( x + 1)( x 2 + 1) x +1 x +1
2
1 1 1 1 1 1 2x − 1 ≡ A (x 2 + 1) + (Bx + C) (x + 1)
=   x −  x 3 +  x 5 + −  x 2 +  x 4
2 2 2 2 2 2 3
Let x = −1:  −3 = A (2) ⇒  A = −
1 1 1 1 1 2
= + x − x2 − x3 + x4 −3
2 2 2 2 2 3
+ B  ⇒ B =
Coefficients of x 2: 0 = A + B =
2 2
Ans: 1 + x + x 4  for −1 < x < 1
−3 1
Constant terms:  −1 = A + C = +C ⇒C=
2 2
3−x A Bx + C
7. a) ≡ + 3x + 1 3
(1 − 2 x )(1 + x 2 ) 1 − 2x 1 + x2 Ans: −
2( x 2 + 1) 2( x + 1)
3 − x ≡ A (1 + x 2) + (Bx + C) (1 − 2 x) 1 4x +1

x = :  3 −

1 1
= A ⎛⎜1 + ⎞⎟, 
1 5 5
= A   ⇒A=2
2 2
) 1+
3. x − x − 2 x + 3x − 1    ( x − 2)( x + 1)
2 2 ⎝ 4⎠ 2 4 x2 − x − 2
4 x +1

Coefficients of x 2:  0 = A − 2B = 2 − 2B 
4x + 1 A B
⇒B=1 ≡ +
( x − 2)( x + 1) x –2 x +1
Constant terms:     3 = A + C = 2 + C 
⇒C=1 4x + 1 ≡ A(x + 1) + B(x − 2)
2 x +1 Let x = 2:    9 = A (3)   ⇒ A = 3
Ans: +
1 − 2x 1 + x 2 Let x = −1:  −3 = B (−3)   ⇒ B = 1
3 1
Ans: 1 + +
( −1)( −2) x −2 x +1
2(1 − 2x)−1 = 2
b)  [1 + (−1) (−2x) + (−2x)2 +
2 3x + 1 A B C
4. Let = + +
( −1)( −2)( −3) ( x − 1) ( x + 2)
2
x – 1 ( x – 1)
2
x +2
(−2 x )3 + …]
3×2
3x + 1 = A(x − 1)(x + 2) + B(x + 2) + C(x − 1)2
= 2 + 4x + 8x  + 16x  +…
2 3
4
Let x = 1:  4 = B(3)  B =
(x + 1) (1 + x 2)−1 = (x + 1) [1 + (−1) (x 2) 3
−5
( −1)( −2) 2 2
Let x = − 2: −5 = C (−3)2 ⇒ C =
+ ( x ) + …] 9
2 5 5
Coefficients of x2: 0 = A + C = A −  ⇒ A =
= (x + 1) (1 − x 2 + x 4 +…) 9 9
5 4 5
Ans: + −
= x (1 − x2 +...) + 1(1 − x2 +...) 9( x − 1) 3( x − 1)2 9( x + 2)

= x − x3 + 1 − x2 = 1 + x − x2 − x3 32 + 45 x − 8 x 2 A B C
5. Let ≡ + +
10( x + 3)( x − 2)(2 x − 1) x + 3 x – 2 2x − 1
2 + 4x + 8x 2 + 16x 3 + 1 + x − x 2 − x 3
32 + 45x − 8x 2 ≡ 10A(x−2)(2x−1)
    Ans:  = 3 + 5x + 7x 2 +…
+ 10B(x + 3)(2x−1) + 10C(x + 3)(x−2)

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 10
Let x = 2:  32 + 90 − 32 = 10B(5)(3),  90 = 150B −2
1 ⎛ 5 ⎞
−2

9. (2 − 5x)−2 = 2−2 ⎛⎜ 1 − x ⎟⎞ = ⎜ 1 − x ⎟
5
90 3 ⎝ 2 ⎠ 4 ⎝ 2 ⎠
⇒B= =
150 5 2
1 ⎛ –5 ⎞ ( −2)( −3) ⎛ 5 ⎞
Let x = −3:  32 – 135 − 72 = 10A (−5)( −7), =  [1 + (−2) ⎜ x⎟+ ⎜− x ⎟
4 ⎝ 2 ⎠ 2 ⎝ 2 ⎠
−175 −1
−175 = + 350A  ⇒ A = = −5
3
350 2 + ( −2)( −3)( −4 ) ⎛⎜ x ⎞⎟ +….]
3×2 ⎝ 2 ⎠
1 45 8 ⎛ 7 ⎞ ⎛ −3 ⎞
Let x = :    32 + − = 10C ⎜ ⎟ ⎜ ⎟,
2 2 4 ⎝ 2 ⎠⎝ 2 ⎠ 1 75 125 3
1 1
= [1 + 5x + x 2 + x +...]
4 4 2
52 = − 52C  ⇒ C = −1
2 2

1 3 1 1 5 75 125 3
Ans: − + − = + x + x2 + x +…
2( x + 3) 5( x − 2) 2 x − 1 4 4 16 8

96 + 12 x − 5 x 2 A B C −2 2
6. Let ≡ + + for <x<
( x + 4 )2 ( x − 4 ) x+4 ( x + 4) 2
x – 4 5 5
⎛ 1 ⎞ ⎛ −1 ⎞
96 + 12x − 5x 2 ≡ A
 (x + 4)(x − 4) + B (x − 4) 1 ⎜ ⎟⎜ ⎟
⎛1⎞ ⎝ 2 ⎠⎝ 2 ⎠
10. a) (1 − x ) = 1 + ⎜ ⎟ (−x) +
2 (−x)2
+ C (x + 4)2 ⎝2⎠ 2

Let x = 4:   96 + 48 − 80 = C (8)2,  64 = 64C  1 ⎛ −1 ⎞ ⎛ −3 ⎞


⎜ ⎟⎜ ⎟
⇒C=1 2 2 2
+ ⎝ ⎠ ⎝ ⎠ (−x)3 + ….
Let x = −4:  96 – 48 − 80 = B (−8), −32 = −8B  3×2
⇒B=4 1 1 2 1
=1− x − x − x 3 + ...
2 8 16
Coefficients of x 2: −5 = A + C = A + 1 ⇒ A = −6
4 for −1 < x < 1
−6 1
Ans: + +
x+ 4 ( x + 4 )2 x −4  b)  1 − x = 0.9,  1 − 0.9 = x,  x = 0.1
7 x 2 + 8 x − 11 Ax + B C
7. Let 2 ≡ + 1
1 1 1
( x − 2)( x + 3) x −2
2
x +3 ∴(0.9 ) 2 = 1 − (0.1) − (0.1.)2 − (0.1)3 +...
2 8 16
7x 2 + 8x − 11 ≡ (Ax + B)(x + 3) + C (x 2 − 2) = 1 − 0.05 − 0.00125 − 0.0000625
Let x = −3:  63 – 24 − 11 = C (9 − 2),
= 0.9486875 = 0.9487 (4 d.p.)
28 = 7C  ⇒ C = 4
Coefficients of x 2:  7 = A + C = A + 4   ⇒ A = 3 11. (4 + 3x)−3 = 4−3 1 + ( 3
4
x) −3
=
1
64 ( 3
1+ x
4 )
−3

Constant terms:  −11 = 3B − 2C = 3B − 8  ⇒ B = −1 2

Ans:
3x − 1
+
4 =
1
64
[ ⎛ 3 ⎞ ( −3)( −4 ) ⎛ 3 ⎞
1 + (−3) ⎜ x ⎟ +
⎝4 ⎠ 2
⎜ x ⎟ + ...
⎝4 ⎠ ]
x −2
2
x −3
5 =
1
[ 9 27
1 − x +  x 2 +… ]
)
8. x − 2 x + x 5 x − 11x + 7 x − 3
3 2 3 2 64 4 8

5 x 3 − 10 x 2 + 5 x 1 9 27 2 −4 4
= − x+ x  +…  for <x<
x + 2x −3
2 64 256 512 3 3

−x 2 + 2x − 3
5 +
x ( x − 1)2 ∴ A = 5
−x 2 + 2x − 3 C D
Let ≡B + +
x ( x − 1)2 x x −1 ( x − 1)2

−x 2 + 2x − 3 ≡ B (x − 1)2 + C x (x − 1) + D (x)


Let x = 0:  −3 = B (−1)2   ⇒ B = −3
Let x = 1:  −2 = D (1)    ⇒ D = −2
Coefficients of x 2:  −1 = B + C = −3 + C  ⇒ C = 2
Ans: A = 5, B = −3, C = 2, D = −2

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 11
( −1)( −2)
1 −1 −
1

1 3(1 + x)−1 = 3 [1 + (−1) (x) +
b) (x)2
⎛ 1 ⎞ 1
= ⎛⎜ 1 + x ⎞⎟
− 2 1 2
2
12. a) ( 4 + 2 x ) 2
=4 2
⎜1 + x ⎟
⎝ 2 ⎠ 2⎝ 2 ⎠ ( −1)( −2)( −3)
+ (−x)3 +…]
3×2
1 ⎛ −1 ⎞ ⎛ 1 ⎞
=  [1 + ⎜ ⎟ ⎜ x ⎟ = 3 − 3x + 3x2 + 3x3 +…
2 ⎝ 2 ⎠⎝2 ⎠
−1 −1
1
(2 + x)−1 = −2−1 ⎛⎜ 1 + ⎞⎟ = − ⎛⎜ 1 + ⎞⎟
x x
⎛ −1 ⎞ ⎛ −3 ⎞
⎜ ⎟ ⎜ ⎟ ⎛ 1 ⎞2 ⎝ 2⎠ 2⎝ 2⎠
+ ⎝ 2 ⎠⎝ 2 ⎠ ⎜ x ⎟
2 ⎝2 ⎠ 1 ⎛x⎞ ( −1)( −2) ⎛ x ⎞
2

= [1 + (−1) ⎜ ⎟ + ⎜ ⎟
⎛ 1 ⎞ ⎛ −3 ⎞ ⎛ −5 ⎞ 2 ⎝2⎠ 2 ⎝2⎠
⎜ − ⎟ ⎜ ⎟ ⎜ ⎟ ⎛ 1 ⎞3
+ ⎝ 2 ⎠ ⎝ 2 ⎠ ⎝ 2 ⎠ ⎜ x ⎟ +...] ( −1)( −2)( −3) ⎛ x ⎞
3

3×2 ⎝2 ⎠ + ⎜ ⎟ +…]
3×2 ⎝2⎠
=
1
2 [1
4
3
1 − x + x2 −
32
5 3
128
x ] =
1 1 1 1
− x + x 2 − x 3 +…
2 4 8 16
1 1 3 2 5 3
= − x+ x − x +… 5 11 23 2 47 3
2 8 64 256 
Ans: − x + x − x +… for −1< x <1
2 4 8 16
for −2 < x < 2
3x 2 − x + 4 A B C
15. a) ≡ + +
 b)   4.02 = 4 + 2x,  0.02 = 2x,  x = 0.01 (1 + x )(1 − x )2 1+ x 1– x (1 – x )2
1
44.02
.02

2 =
1 1 3
− (0.01) + (0.01)2 −
5
(0.01)3 3x 2 − x + 4 ≡ A(1 − x)2 + B (1 + x) (1−x)

2 8 64 256 + C (1 + x)

=0
 .5 − 0.001 25 + 0.000 004 687 5 
Let x = −1:  3 + 1 + 4 = A (2)2, 8 = 4A 
⇒A=2
− 0.000 000 019 53

Let x = 1:    3 − 1 + 4 = C (2)     
= 0.498 754 67 (8 d.p.) ⇒C=3
1 
Coefficients of x 2:    3 = A − B = 2 − B 
13. (2 − x)(1 − 2 x ) 2  ⇒ B = −1

[1
 = (2 − x) 1 + (−2x) +
2
⎛ 1 ⎞ ⎛ −1 ⎞
⎜ ⎟⎜ ⎟
⎝ 2 ⎠⎝ 2 ⎠
2×1
(−2x)2
Ans:
2
1+ x

1
1– x
+
3
(1 – x )2

]
( −1)( −2) 2
1 ⎛ −1 ⎞ ⎛ −3 ⎞  b)   2(1 + x)−1 = 2[1 + (−1)x + x  +…]
⎜ ⎟⎜ ⎟ 2
2 2 2
+ ⎝ ⎠ ⎝ ⎠ (−2x)3 +.. = 2 − 2x + 2x 2 +….
3×2 ( −1)( −2)
−1(1−x)−1 = −1[1 + (−1)( −x) + (−x)2
[ 1 1
 = (2 − x) 1 − x − x 2 − x 3 +…
2 2 ] +…]
= −1 − x − x 2 −…
2

[ 1 1
 = 2 1 − x − x 2 − x 3 +... − x 1−x− x 2 + ...
2 2 ] [ 1
2
1
3 ] 3(1 − x)−2 = 3 [1 + (−2)( −x) +
= 3 + 6x + 9x 2+…
( −2)( −3)
2
(−x)2 +..]

2 2 1
 = 2 − 2x − x 2 − x 3 − x + x 2 + x 3 + .... Ans: 4 + 3x + 10x 2 +…  for −1 < x < 1
2 2 2
1 −1 1
 = 2 − 3x− x 3… for <x<
2 2 2

2x + 5 A B
14. a) ≡ +
(1 + x )(2 + x ) 1+ x 2+x

2x + 5 ≡ A (2 + x) + B (1 + x)
Let x = −1: −2 + 5 = A (2 − 1) ⇒ A = 3

Let x = −2: −4 + 5 = B (1 − 2) ⇒ B = −1
3 1
Ans: −
1+ x 2+x

© Oxford University Press 2018: this may be reproduced for class use solely for the purchaser’s institute Further algebra 12

You might also like